Exploring Training to Use Technology Enhanced Learning in a Uruguayan School of Primary Teachers - Gottlieb, Camila (2017)
This study attempted to investigate how are Uruguayans future Primary teachers learning how to teach with technology in a country that is commemorating 10 years’ anniversary of their OLPC Program called ‘Plan Ceibal’. A case study was chosen to answer the research questions, documents analysis and interviews were the methods selected. Seventeen people were interviewed, teachers and advanced students of an Uruguayan School of Teachers. Data analysis revealed that current approaches to learning about how to teach with technology are quite basic and technology is treated as an isolated subject, furthermore, Plan Ceibal opportunities are not being fully exploited. Most of the teachers use technology to support their lectures and according to participants, it is barely used in their School of Practices, therefore, students do not have many examples where technology is integrated. Students mentioned they feel their learning is not enough and is outdated. Findings of the study show there is a need to improve not only the teachers’ attitudes towards technology but also their training. Moreover, teachers who integrate technology into their classes and encourage their students to include technology into their practices should be rewarded. Instances to reflect on the role of technology and how current teaching methods could be innovated should also be considered.